Corporate Governance at the World Bank and the Dilemma of Global Governance - Kaja, Ashwin (World Bank, 2012)
Most major decisions at the World Bank are made by its Board of Executive Directors. While some countries enjoy the opportunity to serve on this powerful body, most countries rarely, if ever, get that chance. This gives rise to the question: Does board membership lead to higher funding from the World Bank's two main development financing institutions, the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA). Empirical analysis shows that developing countries serving on the board can expect more than double the funding from the IBRD as countries not on the board. In absolute terms, countries on the board receive an average $60 million “bonus” in IBRD loans, an amount that rises in years when IBRD loans are in high demand, particularly for countries in the most influential seats. This effect is more likely driven by informal rules and norms in the boardroom than by the power of the vote itself. No significant effect is found in IDA funding. These results point to challenges of global governance through representative institutions.